2020
DOI: 10.1155/2020/8881416
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Behavior and Energy Evolution of Sandstone considering Slenderness Ratio Effect

Abstract: To study the influence of slenderness ratio effect on the mechanical behavior, acoustic emission properties, and energy evolution of sandstone, the uniaxial compression tests coupled with acoustic emission technology are carried out at different slenderness ratios D (0.5, 1.0, 1.5, 2.0, 3.0). The results show that a logarithmic function relationship is observed between the peak strength, the peak strain, and the elastic modulus with slenderness ratio. The failure patterns of the tested sandstone varied signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…For example, Zhang et al (2019) established different mineral size models by using the DEM, and obtained a fourth-order polynomial relationship between the rock elastic modulus and the model radius. Dai et al (2020) found that the relationship between the elastic modulus and the slenderness ratio accords with a logarithmic function using uniaxial compression tests. Ma et al (2021) used PFC to simulate the uniaxial compression of coal and rock composite samples with different height-ratios, and obtained that the elastic modulus has an exponential relationship with the height-ratios of coal-rock.…”
Section: Introductionmentioning
confidence: 82%
“…For example, Zhang et al (2019) established different mineral size models by using the DEM, and obtained a fourth-order polynomial relationship between the rock elastic modulus and the model radius. Dai et al (2020) found that the relationship between the elastic modulus and the slenderness ratio accords with a logarithmic function using uniaxial compression tests. Ma et al (2021) used PFC to simulate the uniaxial compression of coal and rock composite samples with different height-ratios, and obtained that the elastic modulus has an exponential relationship with the height-ratios of coal-rock.…”
Section: Introductionmentioning
confidence: 82%
“…Liu et al (2019a) indicated that multiscale has the greatest impact on peak strength and E based on acoustic emission research. Wang et al (2020) discovered that the smaller the initial crack density, the greater E. Dai et al (2020) discussed the relationship between E and the slenderness ratio for the height-diameter ratio. Ma et al (2021) explored the effect of the height-diameter ratio of coal petrography from 4:1 to 1:4 on Zhang et al (2020), andLiu et al (2019b) investigated the change in heightdiameter ratio and concluded that E is positively correlated with height-diameter ratio.…”
Section: Introductionmentioning
confidence: 99%